1991
DOI: 10.1246/cl.1991.1429
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Novel Tetranuclear and Binuclear Manganese(III) Complexes with 1,5-Bis(salicylideneamino)-3-pentanol

Abstract: Tetranuclear and binuclear manganese(III) complexes with 1,5-bis(salicylideneamino)-3-pentanol (H3L), [Mn4(L)2(O)2(CH3COO)2]·4H2O·2CH3OH and [Mn2(L)(CH3O)(NCO)2(H2O)2], have been prepared and characterized by X-ray structure analysis and magnetic susceptibilities (80–300 K).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 10 publications
1
10
0
1
Order By: Relevance
“…The solid line in Fig. 3 represents the best fit with the following parameters J = À12.4 cm À1 , g = 1.98, p = 0.5% and TIP = 360 · 10 À6 cm 3 mol À1 K. The calculated exchange parameter J is in keeping with the values observed for other dialkoxo bridged Mn III dimers with Jahn-Teller elongation perpendicular to the Mn III -l-O-alkoxo axis and similar short MnÁ Á ÁMn distances (within the range 2.98-3.00 Å ) [52,[54][55][56]. On the other hand, the alkoxo bridged Mn III dimers [Mn III (5-NO 2 sal- …”
Section: Magnetic Susceptibilitysupporting
confidence: 78%
“…The solid line in Fig. 3 represents the best fit with the following parameters J = À12.4 cm À1 , g = 1.98, p = 0.5% and TIP = 360 · 10 À6 cm 3 mol À1 K. The calculated exchange parameter J is in keeping with the values observed for other dialkoxo bridged Mn III dimers with Jahn-Teller elongation perpendicular to the Mn III -l-O-alkoxo axis and similar short MnÁ Á ÁMn distances (within the range 2.98-3.00 Å ) [52,[54][55][56]. On the other hand, the alkoxo bridged Mn III dimers [Mn III (5-NO 2 sal- …”
Section: Magnetic Susceptibilitysupporting
confidence: 78%
“…3) was obtained with the following parameters: J = À13.1 cm À1 , g = 1.90 and p = 0.2%. The calculated exchange parameter J falls in the range observed for other dialkoxo bridged diMn III complexes with short MnÁ Á ÁMn distances (2.98-3.00 Å ) [18,19,27,[34][35][36][37] that allow direct overlap between the d xy orbitals.…”
Section: Magnetic Propertiesmentioning
confidence: 54%
“…The elucidation of the crystal structures of oxygen-evolving photosystem II from Thermosynechococcus elongatus at 3.8 Å resolution by Zouni et al [5] and Thermosynechococcus vulcanus at 3.7 Å resolution by Kamiya and Shen [6], respectively, indicated that a tetranuclear manganese center is at the heart of the water splitting reaction, triggered efforts toward the synthesis of structural and functional analogues of the oxygen-evolving complex. The three general classes of tetranuclear manganese complexes with variable oxidation states which are synthesized are (i) the [Mn 4 (l 3 -O) 2 ] core using the carboxylate aggregate developed by Christou and Hendrickson [7][8][9] (ii) the [Mn 4 (L) 2 (O) 2 (CH 3 COO) 2 ] core where L = the schiff base ligands 2,6-bis(salicylideneaminomethyl)-4-methylphenol or 1,5-bis-(salicylideneamino)-3-pentanol or 2,6-bis(N-(4-imidazolylethyl)iminomethyl]-4-methylphenol reported by Mikuriya et al [10][11][12][13] and (iii) the inorganic analogues of M 2+ (12-crown-4) such as Mn(II)[Mn(III)-salicylhydroximate] 4 described by Pecoraro et al [14,15] In all the above cases the Mn 4 (III) aggregate is formed with the participation of ancillary bridging ligands such as acetato-, benzoato-, etc. Herein we report the X-ray structure of a neutral tetranuclear Mn(III) cluster containing The article was accepted and intended for the Special issue but was left out due to a production error.…”
Section: Introductionmentioning
confidence: 99%